2010
DOI: 10.1590/s1516-44462010000100011
|View full text |Cite
|
Sign up to set email alerts
|

Performance of schizophrenic patients in the Stroop Color Word Test and electrodermal responsiveness after acute administration of cannabidiol (CBD)

Abstract: Objective: The last decade has seen increasing evidence of dysfunctions in the endogenous cannabinoid system in schizophrenia and of its relationship with the typical cognitive impairment of the disorder. Studies in animal models, healthy volunteers, and psychotic patients clearly suggest an antipsychotic-like effect of cannabidiol. This study investigated the effects of cannabidiol on selective attention in 28 schizophrenic patients using the Stroop Color Word Test and on these patients' electrodermal respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 29 publications
2
90
0
7
Order By: Relevance
“…This drug induces psychotic symptoms that mimic both positive and negative symptoms of schizophrenia. An initial investigation in healthy subjects showed that CBD induced a non-significant trend to reduce ketamine-induced dissociative effects, but, at the same time, augmented the activating effects of ketamine (28) 300 and 600 mg (acute) no effect [106] [102]. Because only a single dose of CBD was used, additional studies are needed to characterize the effects of CBD in this model [102].…”
Section: Cannabidiol and Psychosismentioning
confidence: 99%
See 1 more Smart Citation
“…This drug induces psychotic symptoms that mimic both positive and negative symptoms of schizophrenia. An initial investigation in healthy subjects showed that CBD induced a non-significant trend to reduce ketamine-induced dissociative effects, but, at the same time, augmented the activating effects of ketamine (28) 300 and 600 mg (acute) no effect [106] [102]. Because only a single dose of CBD was used, additional studies are needed to characterize the effects of CBD in this model [102].…”
Section: Cannabidiol and Psychosismentioning
confidence: 99%
“…One patient showed mild improvement, but only slight or no change was observed in the other two, suggesting that CBD may not be effective for the treatment of resistant schizophrenia. Moreover, CBD had no beneficial effects on the performance of schizophrenic patients in the Stroop colour word test, which can be used to assess attentional processes frequently impaired in schizophrenia [106]. It is still unknown whether chronic administration of CBD could improve the cognitive deficits in the disorder.…”
Section: Cannabidiol and Psychosismentioning
confidence: 99%
“…In einer kontrollierten Studie mit 28 SchizophreniePatienten konnte bei einmaliger Gabe von 300 und 600 mg CBD mit dem «Farbe-Wort-Interferenz-Test nach Stroop» im Vergleich zu «keiner Therapie» keine Wirkung festgestellt werden [17].…”
Section: Schizophrenie/psychotische Symptome Bei Schizophrenieunclassified
“…Hallak et al studied the acute effects of CBD on selective attention, as well as electrodermal responsiveness to auditory stimuli, in 28 medication-free schizophrenic patients. They found no differences on any measure between patients who received a single oral dose of CBD 300 mg, CBD 600 mg, or placebo [94]. Finally, the largest clinical study of the effects of CBD on psychosis to date was a 4-week, double-blind, randomized trial comparing CBD, up to 800 mg per day (n=20), to the antipsychotic amisulpride (n=19).…”
Section: Cbdmentioning
confidence: 99%